P89 Comparison of aerosol drug delivery across delivery devices in a spontaneously breathing asthmatic paediatric patient model. (11th November 2022) - Murphy, S; Reilly, L; O'Sullivan, O; Mac Giolla Eain, M; Joyce, M; MacLoughlin, R
Abstract : Introduction and Objectives: Aerosol therapy is often used in the treatment of asthma exacerbations in paediatric patients. Standard dosing regimens differ depending on the type of aerosol generator used. Here, we assess drug delivery using a pressurised metered dose inhaler (pMDI) and a vibrating mesh nebuliser (VMN) in a simulated asthmatic paediatric patient. Methods: The standard dose for a pMDI (TEVA Salamol CFC-Free Inhaler, IRE) is 4 actuations, delivering 400µg of Salbutamol at the start of inhalation. This was delivered through a valved holding chamber/facemask (Monaghan Medical, US). For the VMN, 2500µg Salbutamol (TEVA, IRE) was nebulised in combination with an aerosol chamber and facemask (Aerogen Solo/Ultra, Aerogen, IRE) with a supplemental gas flow of 2 LPM. Both devices were attached to a breathing simulator (ASL 5000, IngMar Medical, US) via a 3D printed paediatric head model (oropharyngeal, 5-year-old male) [2] and capture filter (Respirgard 303, Vyaire, US), that was set to simulate an asthmatic paediatric patient (Vt : 186 mL, 28BPM and I:E: 1:2) [3]. Results were determined using UV-spectroscopy at 276 nm and are expressed as µg of drug delivered. All tests were conducted in quintuplicate. Results: Conclusions: The VMN delivered a significantly larger drug dose (p-value: 0.000). These findings demonstrate that the type of drug delivery device used has a considerable impact on aerosol delivery to a simulated patient and may prevent escalation of care. References: The Impact of Head Model Choice on the In Vitro Evaluation of Aerosol Drug Delivery. Pharmaceutics . 2021;14. ASL 5000 User Manual, Software 3.6, IngMar Medical, Ltd. 2016. Available from: ASL 5000_User's Manual _SW 3.6 (ingmarmed.com) .